2007
DOI: 10.1017/s0022215107000540
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between tuberculous otomastoiditis and tuberculous meningitis

Abstract: Tuberculous meningitis is frequently accompanied by otomastoiditis, although the exact causal relationship between the two conditions is unclear. Since meningitis is a serious clinical condition, concomitant otomastoiditis generally remains unrecognised. Tuberculosis should be considered in the differential diagnosis of patients with otitis or otomastoiditis who do not respond to antibiotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…4). Intracranial complications of otomastoiditis is even rarer and include meningitis, encephalitis, empyema, extradural collections and sinus venous thrombosis [5], which makes the management of such cases extremely challenging. And out of paediatric case reports presented, only one was found to have reported intracranial complications [6].…”
Section: Discussionmentioning
confidence: 99%
“…4). Intracranial complications of otomastoiditis is even rarer and include meningitis, encephalitis, empyema, extradural collections and sinus venous thrombosis [5], which makes the management of such cases extremely challenging. And out of paediatric case reports presented, only one was found to have reported intracranial complications [6].…”
Section: Discussionmentioning
confidence: 99%
“…Vaamonde et al diagnosed 10 cases from 1996 to 2002 in Spain (6). A more recent study from Turkey found tuberculous otomastoiditis in 11 of 32 (34%) patients with tuberculous meningitis (9). Laryngitis and otitis media remain the most frequent ear, nose, and throat diseases of tuberculous origin (10).…”
Section: Incidencementioning
confidence: 99%
“…Extension and hematogenous dissemination from tuberculous otomastoiditis are rare, as evidenced by the frequent chronicity of the disease for many years without such spread (6). The dura mater usually resists direct extension to the brain; however, tuberculous meningitis is definitely associated with chronic tuberculous otomastoiditis (9,21,22). Evaluation for pulmonary involvement can be useful, as up to 50% of patients with tuberculous otomastoiditis may have X-ray evidence of pulmonary tuberculosis (11).…”
Section: Diagnosismentioning
confidence: 99%
“…16 However, a recent study found a higher incidence of TB otomastoiditis (34.3%) among patients who were diagnosed with TB meningitis, indicating that although the exact causal relationship remains unclear, TB meningitis is frequently accompanied by TB otomastoiditis. 25 Contemporary studies indicate that TBOM has no typical clinical presentation. In fact, it can have variable and insidious features with a chronic, indolent course.…”
Section: Review Of the Clinical Presentationsmentioning
confidence: 99%
“…Lack of responsiveness to standard therapy for otitis media including the use of antibiotics, whether topical or systemic, has been consistently reported to be an indication for suspecting tuberculous otitis media. 13,25,29 One of the cases included in the local series 14 was even given intravenous amoxicillin plus clavulanic acid prior to the decision to submit the patient to surgery, which nevertheless resulted to failure in the relief of ear discharge. Another patient was given several weeks of oral amoxicillin plus clavulanic acid for four weeks and had myringotomy with ventilation tube insertion which resulted to the extrusion of the ventilation tube after less than a month.…”
Section: Review Of the Diagnosis Of Tb Otitis Mediamentioning
confidence: 99%